The accretionary Svecofennian orogen — insight from the BABEL profiles - Korja, Annakaisa; Heikkinen, Pekka (Precambrian Research, 2005)
The BABEL profiles B, C, 1–7 form a 1200 km long nearly continuous cross-section through the Svecofennides. The near-vertical marine reflection profiles display a wide range of crustal structures that can be associated with both the accretionary Svecofennian orogeny (1.96–1.75 Ga) and the following Subjotnian and Jotnian rift-stages (1.65–1.11 Ga). The Svecofennian accretionary orogeny took place when a number of micro-plates with island arc affinities and surface expression of a large archipelago accreted to the continental Karelian plate. Some of the accreting terranes seem to have had older cores that have acted as crustal indentors during the collision. BABEL profiles 3 and 4 image a series of collisional terrane boundaries between Karelian continental margin, Savo arc (SA) and Central-Finland arc (CFA). In the north, the Karelian margin has been both over- and underthrust by the Savo arc. CFA comprises a folded thrust package on top of a continental nucleus and the Savo arc. The associated subduction zone and accretionary prism are interpreted to lie to the south, underneath the Bothnian basin area, where prominent NE-dipping, lower to middle crustal reflections are found along BABEL profiles 1 and 4. An oblique collision of the Central Finland arc and the continent resulted in the development of the strike-slip fault on the young, hot Savo arc. BABEL profiles 1, 6, 7 and C image the internal architecture of the Southern and Central Finland arcs. The unusually thick crust (55–60 km) hosts unreflective, high density, mafic intrusions acting as a crustal indentor. A highly reflective antiform structure developed on the southern side of it. Southern Finland arc complex (SFA) is an imbrication structure comprising stacked slices of arc-related crust on an older continental nucleus, Bergslagen nucleus. Prior to the collision, the SFA suffered from gravitational collapse during which the crust was thinned. Profile B images the architecture of the Central and Southern Swedish Svecofennides. The Sörmland terrane ...